When the wicked seize a city - McIlhenny, Chuck; McIlhenny, Donna; York, Frank (Lafeyette, LO Huntington House, 1993)
Includes bibliographical references.
Donated by Pieter Dijkstal, 5/2003.
Keywords: Homosexuality -- ethics; Gay rights -- ethics